ANALISIS PESAN ANTI RASISME DALAM FILM DEAR WHITE PEOPLE - Reni Juliani (SOURCE : Jurnal Ilmu Komunikasi, 2018)
This study aims to find out what messages are contained in the film Dear White People. Peircesemiotics theory is the underlying theory of this research. This theory deals with indentifying,documenting, and classifying the main types of signs and how they are used in representativeactivities. Messages ini movies usually depict events or phenomena that are all around us, suchas warfare, romance, munder, mafia crimes, rasism, anti rasism and more.a good movie is amovie that has the contents of a message that can be used as inspiration by the movie lovers. Amovie can be said to be quality if the theme and content of the message contains a positive andstrong meaning. From the result of this study found that the film Dear White People directed byJustin Simien has a message that oppression, discrimination or exclusion of a group, people orgroups both minority and majority is a form of racism.the struggle against racism bysuppressing the majority with the stereotype that the majority always oppress the minority is anew from of racism.Keywords: Message, Anti Rasisme,Film.